New patients with Temple syndrome caused by 14q32 deletion: Genotype‐phenotype correlations and risk of thyroid cancer. Issue 1 (3rd September 2015) - Severi, Giulia; Bernardini, Laura; Briuglia, Silvana; Bigoni, Stefania; Buldrini, Barbara; Magini, Pamela; Dentici, Maria L.; Cordelli, Duccio M.; Arrigo, Teresa; Franzoni, Emilio; Fini, Sergio; Italyankina, Eleonora; et al.
Abstract : Temple syndrome (TS) is caused by abnormal expression of genes at the imprinted locus 14q32. A subset of TS patients carry 14q32 deletions of paternal origin. We aimed to define possible genotype‐phenotype correlations and to highlight the prevalence of thyroid dysfunction, which is a previously unreported feature of TS. We described four new patients who carry deletions of paternal origin at 14q32 detected by array‐CGH and reviewed nine patients reported in the medical literature. We compared clinical features with respect to deletion size and position. Expression of DLK1 is altered in all the patients with TS, but intellectual disability (ID) is present only in patients with larger deletions extending proximally to the imprinted locus. This study led to the identification of an ID "critical region" containing four annotated genes including YY1 as the strongest candidate. Furthermore, we described three patients with thyroid dysfunction, which progressed to papillary carcinoma at a very young age in two of them. We conclude that DLK1 loss of function is likely to be responsible for the core features of TS, while haploinsufficiency of a gene outside the imprinted region causes ID. Thyroid cancer may be an unrecognized feature and monitoring for thyroid dysfunction should thus be considered in TS patients. © 2015 Wiley Periodicals, Inc.